"Who sings put his/her troubles away.": the sound-musical language in early childhood education. - Juliana Schumacker Lessa; Melina Kerber Klitzke; Paulo Sérgio da Graça Delgado (Universidade Federal de Santa Catarina, 2014)
This article portrays the internship experience in early childhood education of a student and a student of Pedagogy of the Federal University of Santa Catarina (UFSC), which was held at Brother Celso daycare with a group of children aged 3 to 4 years (G4) in the first half of 2013. We report the experience of being teacher of young children, along with the proposal to work with sound and musical language. This experience confirmed children as subjects producers of children's cultures, in that besides meaning they resignify objects, actions and situations giving them new functions, new meanings.